2015
DOI: 10.1007/s15010-015-0867-6
|View full text |Cite
|
Sign up to set email alerts
|

Herpes simplex and varicella zoster CNS infections: clinical presentations, treatments and outcomes

Abstract: Alpha herpes CNS infections due to HSV and VZV infections have similar clinical and laboratory manifestations. ACO was observed more frequently in those patients with comorbidities and an encephalitis presentation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
75
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(79 citation statements)
references
References 39 publications
2
75
0
2
Order By: Relevance
“…Similarly, even with the increased sensitivity of PCR, HSV was detected in only 6.2% of 6,607 CSF samples at the Mayo Clinic from 1993 to 1997 (35). Cutaneous manifestations of HSV in patients with HSV CNS involvement have been reported to be present in Ͻ10% of cases (36)(37)(38). Therefore, detection of HSV at other sites is not necessarily predictive of CNS involvement.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, even with the increased sensitivity of PCR, HSV was detected in only 6.2% of 6,607 CSF samples at the Mayo Clinic from 1993 to 1997 (35). Cutaneous manifestations of HSV in patients with HSV CNS involvement have been reported to be present in Ͻ10% of cases (36)(37)(38). Therefore, detection of HSV at other sites is not necessarily predictive of CNS involvement.…”
Section: Discussionmentioning
confidence: 99%
“…Of the infectious causes, HSVE was the most commonly identified agent, followed by tuberculosis and VZV. In the absence of zoster, HSV and VZV can be clinically indistinguishable [94]. More than half of the noninfectious etiologies were immune-mediated, including anti-N-methyl-D-aspartate receptor (NMDAR) encephalitis, antivoltage-gated potassium channel complex encephalitis (more precisely anti-leucine-rich glioma-inactivated protein 1 [LGI1] and anti-contactin-associated protein-like 2 [Caspr2] antibodies), and CNS vasculitis.…”
Section: Differential Diagnosismentioning
confidence: 99%
“…It has been demonstrated that signs and symptoms alone do not distinguish herpes from other causes of encephalitis (1,5,6). Therefore, an integrative diagnostic approach with the full utilization of neurodiagnostic techniques is a must.…”
Section: Discussionmentioning
confidence: 99%
“…Laboratory findings of encephalitis are characterized with pleocytosis and elevated protein levels (1,2,3,6), with the exception of around 3 to 5 percent of patients with normal CSF analysis despite severe encephalitis, particularly initially (1,2). In our study, CSF pleocytosis was determined in 80.1% of patients, while protein levels were elevated in 57.4% of patients.…”
Section: Discussionmentioning
confidence: 99%